Tinjauan Sistem dan Kinerja Manajemen Keselamatan & Kesehatan Kerja Tambang Bawah Tanah CV. Tahiti Coal, Talawi, Sawahlunto, Sumatera Barat - Rika Almaida Simanjuntak; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2018)
Abstact. Based on data that is obtained from the company, there are 19 cases of accidents that is occurred in 2015-2017. The Causes include the workers who ignore the function of PPE, potential hazards from rock debris and slippery road surface conditions. The purposes of this research are : 1) Reveal the factors that cause accidents at CV. Tahiti Coal. 2) Reveal the percentage of unsafe incidents and unsafe conditions on the CV. Tahiti Coal. 3) Reveal the level of risk of accidents by calculating the number of accident frequency (Frequency Rate) and the severity of the accident (Severity Rate). 4) Revealing Job Hazard Analysis (JHA), Job Safety Analysis (JSA) and SOP in the field of workers in the CV. Tahiti Coal.The collected data is obtained directly by having an interview with the leaders and staff and also the the workers that are related to the object of research. The data is taken from the factors of cause the accident at CV. Tahiti Coal, the number of accidents and how the K3 management system in CV. Tahiti Coal.To avoid the accidents, the company should complete all PPE for workers in accordance with their field of work, and always use PPE when working in accordance with the established SOP.  Keywords: PPE, K3, Accident Risk Level, SOP, JHA